Moisture formation in urea compound via ball milling technique: article - Ahmad Isa, Ain Marseila; Kadri, Atikah (2018)
Moisture formation in urea calcium phosphate (UCP) fertilizer were synthesized by using ball milling technique. Prolonged milling time can cause moisture formation in the presence of moisture in air that makes the mixture wet and sticky. In this study is to find the best optimum milling time to avoid moisture formation of urea compound and to investigate the moisture formed in the compound during milling at 2 to 14 minutes. Physical observation and sample characterization were analyzed by XRay Diffraction (XRD), Thermal Gravimetric Analysis (TGA), and Fourier Transform Infrared (FT-IR) spectroscopy. It is observed that the product is in solid powder form at 2 minutes and become clumpier from 4 to 12 minutes.